Cocaine-induced acute interstitial nephritis: A case report and review of the literature - Rodrigo Alfaro; Nina Vasavada; Paisit Paueksakon; German T. Hernandez; George R. Aronoff (Society of Diabetic Nephropathy Prevention, 2013)
Background: Acute tubular necrosis and pigment induced kidney injury are well described consequences of cocaine abuse. However, acute interstitial nephritis associated with cocaine use has been previously reported in only three patients. Case presentation: We present the case of a 49-year-old man who developed acute kidney injury from biopsy-proven interstitial nephritis after nasal insufflation of cocaine. Unlike prior reports, our patient remained non-oliguric and did not require renal replacement therapy. Conclusions: Interstitial nephritis should be considered as a potential cause of acute kidney injury associated with cocaine use. The approach to management of cocaine associated acute kidney injury (AKI) may be different in patients with interstitial nephritis than for those with tubular necrosis or pigment induced renal injury.